PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTs TI BATANG KABUNG PADANG - Nopriza, Yona - (STKIP PGRI Sumbar, 2014)
This research base on students comprehension of mathematical concepts that were still low. This researchâs purpose is to determine students achievement of understanding mathematical concepts for implementing cooperative learning model snowball throwing with quiz and find out if the students understanding of mathematical concepts by implementing cooperative learning model accompanied quiz snowball throwing better than students understanding of mathematical concepts that use conventional learning in the classroom VIII MTs TI Batang Kabung Padang. This type of research was experiment research. Population in this study were all class VIII MTs TI Batang Kabung Padang. Technique is random sampling, the sample is a class VIIID and class VIIIA. Hypothesis testing using t-test of the parties with the assistance of MINITAB, the P-value obtained is smaller than Î±, so it can be concluded that the students understanding of mathematical concepts using cooperative learning model snowball throwing with quiz better than students understanding of mathematical concepts by using conventional learning in class VIII MTs TI Batang Kabung Padang.